Does Strategic Supply Chain Information System Leads To Efficient Supply Chain and Improved Performance in Indonasin Firms - Syamsiah Badruddin; Zulkarnain Hamson; Suparman Mekka; Ahmad Muktamar B; Zulkarnain . (International Journal of Supply Chain Management, 2020)
The goal of this study is to explore the association among supply chain strategy (SCS) and supply chain information systems (SCIS) strategy and also its influence on efficient supply chain and firm performance (FP). Based on information processing theory (IPT), established hypotheses presenting moderating impact of two supply chain information system strategies (SCIS), information system for efficiency and information system for flexibility. These hypotheses are based on the separate relationship among the two SC approaches i.e. Lean and Agile, and SC efficiency and FP. On the basis of data gathered from top management working in procurement, logistics and SC departments of 250 Indonesian firms, for the survey. The gathered data were analysed by using tools like confirmatory analysis and structural equation modelling (SEM), validated our hypotheses. The result shows that IS for efficiency and flexibility, IS strategy strengthen the association among Lean (Agile) SC strategy and SC efficiency. Moreover, there is positively significant association was revealed among SC efficiency and FP and moderating association among SC efficiency on the association among SC strategy and FP was also found. This research offers novel addition in available research by offering theoretical foundation and supportive results that SC efficiency can be enhanced if SC and IS strategies are implemented simultaneously.